2015
DOI: 10.1007/s11430-015-5076-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture drought detection and multi-temporal variability across China

Abstract: Soil moisture droughts can trigger abnormal changes of material and energy cycles in the soil-vegetation-atmosphere system, leading to important effects on local ecosystem, weather, and climate. Drought detection and understanding benefit disaster alleviation, as well as weather and climate predictions based on the understanding the land-atmosphere interactions. We thus simulated soil moisture using land surface model CLM3.5 driven with observed climate in China, and corrected wet bias in soil moisture simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
(42 reference statements)
1
19
1
Order By: Relevance
“…Previous studies also showed that CLM3.5 produces too-high soil moisture with too-low variability compared to root zone soil moisture modeled by later CLM versions (4.0 and 4.5) (e.g., Lawrence et al, 2011;Niu et al, 2011). In order to reduce these biases, Li and Ma (2015) introduced a factor to describe soil porosity and increase recharge water from the soil column to the aquifer in the newer CLM, leading to improved estimates of soil moisture and biogeochemical processes. However, Lawrence et al (2011) showed that the differences between CLM3.5 and new versions of CLM with respect to soil moisture variability remained small when compared to observations.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Previous studies also showed that CLM3.5 produces too-high soil moisture with too-low variability compared to root zone soil moisture modeled by later CLM versions (4.0 and 4.5) (e.g., Lawrence et al, 2011;Niu et al, 2011). In order to reduce these biases, Li and Ma (2015) introduced a factor to describe soil porosity and increase recharge water from the soil column to the aquifer in the newer CLM, leading to improved estimates of soil moisture and biogeochemical processes. However, Lawrence et al (2011) showed that the differences between CLM3.5 and new versions of CLM with respect to soil moisture variability remained small when compared to observations.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Finally, the new observation-constrained atmospheric forcing data were constructed at 0.5°grid spacing, 3-h interval for a 50-year time span from 1951 to 2000. Several studies have already shown that this observation-constrained atmospheric forcing data can significantly improve the land surface simulations over China (Liu et al 2012;Li and Ma 2015).…”
Section: Atmospheric Forcing Datamentioning
confidence: 96%
“…However, according to Lawrence et al (2011), the soil moisture variability still shows negative bias compared with observations. Based upon the previous assessment of the applicability of CLM 3.5 over China (Li and Ma 2015;Li et al 2016), we opted for CLM 3.5 to simulate the long-term hydroclimatic trends over Xinjiang with enhanced hydrological parameterization in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, CLM 3.5 produces higher soil moisture and lower variability than observations in the rooting zone. To reduce these biases, Li and Ma (2015) introduced a factor to describe soil porosity, increase the recharging water from the soil column to the aquifer, and reduce the flux in the opposite direction, as achieved by Lawrence et al (2011) and Niu et al (2011).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The modeled and observed soil moisture over China agreed well. For instance, the average correlation coefficient is up to 0.83 in Northeast China, where measurements are mostly available for summers during 1990-2000 (statistical details, see Li and Ma 2015).…”
Section: Evaluation Of Runoff Simulationmentioning
confidence: 99%